A Silver Medal Winner at the 13th World Wu Shu Championship 2015 17 Months After Selective Thoracic Fusion for Adolescent Idiopathic Scoliosis: A Case Report. Issue 4 (15th February 2017) - Chan, Chris Yin Wei; Aziz, Izzuddin; Chai, Fong Wei; Kwan, Mun Keong
Abstract : Study Design: Case report. Objective: To report the successful rehabilitation and the training progress of an elite high performance martial art exponent after selective thoracic fusion for Adolescent Idiopathic Scoliosis (AIS). Summary of Background Data: Posterior spinal fusion for AIS will result in loss of spinal flexibility. The process of rehabilitation after posterior spinal fusion for AIS remains controversial and there are few reports of return to elite sports performance after posterior spinal fusion for AIS. Methods: We report a case of a 25-year-old lady who was a national Wu Shu exponent. She was a Taolu (Exhibition) exponent. She underwent Selective Thoracic Fusion (T4 to T12) using alternate level pedicle screw placement augmented with autogenous local bone graft in June 2014. She commenced her training at 3-month postsurgery and the intensity of her training was increased after 6 months postsurgery. We followed her up to 2 years postsurgery and showed no instrumentation failure or lost of correction. Results: After selective thoracic fusion, her training process consisted of mainly speed training, core strengthening, limb strengthening, and flexibility exercises. At 17 months of postoperation, she participated in 13th World Wu Shu Championship 2015 and won the silver medal. Conclusion: Return to elite high-performance martial arts sports was possible after selective thoracic fusion for AIS. The accelerated and intensive training regime did not lead to any instrumentation failure and complications. Level of Evidence: 2